Effective information retrieval from the Internet : an advanced user's guide - Stacey, Alison; Stacey, Adrian; ScienceDirect eBooks (Oxford [England] : Chandos Publishing, 2004)
Effective Information Retrieval from the Internet discusses practical strategies which enable the advanced web user to locate information effectively and to form a precise evaluation of the accuracy of that information. Although the book provides a brief but thorough review of the technologies which are available for these purposes, most of the book concerns practical 'future-proof' techniques which are independent of changes in the tools available. For example, the book covers: how to retrieve salient information quickly; how to remove or compensate for bias; and tuition of novice Internet users.
Fundamentals of information retrieval on the Internet -- Query choice : pinpointing information on the Internet -- Query reformulation, automation and analysis -- Assessing websites for accuracy and bias -- Teaching Internet searching skills to novice users.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Elsevier
Keywords: Information retrieval; Internet searching; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Information retrieval; Internet searching; Information storage and retrieval; Internet; Zoekstrategieën.; Information Retrieval; Internet; Electronic books